2015
DOI: 10.5489/cuaj.2499
|View full text |Cite
|
Sign up to set email alerts
|

Advanced testicular cancer associated with life-threatening tumour lysis syndrome and choriocarcinoma syndrome

Abstract: Tumour lysis syndrome (TLS) and choriocarcinoma syndrome (CS) are severe complications of chemotherapy for testicular cancer. They are rare, but can be life-threatening. A 37-year-old man complaining of persisting cough was referred to our hospital. A computed tomography (CT) scan revealed huge tumours that occupied the peritoneal cavity, with multiple lung, liver, and para-aortic metastases. Although there was no abnormal finding in the testes, serum testicular tumor markers showed marked elevation. A CT-guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 8 publications
0
27
0
Order By: Relevance
“…BEP is a standard chemotherapy regimen for advanced testicular cancers and has been shown to be effective in the management of testicular choriocarcinoma with lung metastases 12 13. In our case, the combination of acute surgery and BEP was shown to have life-saving and curative potential in the treatment of SSIH and of the causative testicular choriocarcinoma with brain metastases.…”
Section: Discussionmentioning
confidence: 59%
“…BEP is a standard chemotherapy regimen for advanced testicular cancers and has been shown to be effective in the management of testicular choriocarcinoma with lung metastases 12 13. In our case, the combination of acute surgery and BEP was shown to have life-saving and curative potential in the treatment of SSIH and of the causative testicular choriocarcinoma with brain metastases.…”
Section: Discussionmentioning
confidence: 59%
“…It has been reported that choriocarcinoma syndrome should be suspected in patients who exhibit high HCG levels, large tumors, and multiple metastases in the early stages of chemotherapy . ARDS due to bleeding from lung metastases has been well characterized, and there have also been reports about bleeding from liver and brain metastases…”
Section: Discussionmentioning
confidence: 99%
“…[1] One of the remarkable features of CC is extensive necrosis so much so that the primary site may sometimes be barely discernible. [1] Necrosis sometimes can give rise to clinically manifest hemorrhage at high tumor-volume metastatic sites, described by Logothetis as choriocarcinoma syndrome,[5] with diffuse alveolar hemorrhage as the most common manifestation. [5] The syndrome portends a poor prognosis[5] and needs early recognition and urgent treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Necrosis sometimes can give rise to clinically manifest hemorrhage at high tumor-volume metastatic sites, described by Logothetis as choriocarcinoma syndrome,[5] with diffuse alveolar hemorrhage as the most common manifestation. [5] The syndrome portends a poor prognosis[5] and needs early recognition and urgent treatment. [5] Our patient underwent hemorrhage within the pleural space followed by the peritoneal cavity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation